An Asymptomatic and Overelongated Styloid Process - Emrah Soylu; Ahmet Altan; Ahmet Ercan Sekerci; Nıhat Akbulut (Hindawi Limited, 2017)
Elongation of the styloid process is a rare condition. Only 4% of patients have clinical symptoms where elongated styloid process (ESP) occasionally irritates or disrupts adjacent anatomical structures, which is called Eagle syndrome. This present report was aimed at reporting an asymptomatic ESP with unusual width and length.